Kepemimpinan Kepala Sekolah dan Profesionalisme Guru Bahasa Arab Pesantren di Kota Lhokseumawe - Aina Salsabila (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2020)
In a number of junior high schools based on the Islamic boarding school in Lhokseumawe city do not have Arabic teachers with educational backgrounds according to their fields of expertise, this will affect the professionalism of teachers in teaching Arabic subjects. The purpose of this study was to explain the leadership style of principal’s Junior High School (MTsS) in carrying out their duties, to descripe the professionalism of Arabic Junior high School (MTsS) teachers in carrying out their duties and to know the influence of principal leadership style on the professionalism of Arabic Junior High School teachers in Islamic boarding school in Lhokseumawe City. The method used is a survey method with a quantitative approach, the sample is 27respondents. Data analyzes using simple linear regression. The results showed that 81% (22 teachers) favored the principal's leadership style and 70% (19 Arabic language teachers) were able to develop their professional competencies. Simple linear regression test results show the significance value for the influence of X on Y is 9,308> 2,055, thus there is a significant influence of school leadership on the professionalism of Arabic MTsS Islamic boarding School teachers in Lhokseumawe.